RELATIONSHIP BETWEEN SCHOOLCHILDREN'S LEVELS OF PHYSICAL ACTIVITY, ANTHROPOMETRIC INDICES AND PULMONARY FUNCTION - Fernanda Pazini; Caroline Pietta-Dias; Cristian Roncada
ABSTRACT Objective: To evaluate and to correlate levels of physical activity with the pulmonary function of children with and without a diagnosis of asthma. Methods: This study was conducted in two phases with schoolchildren aged between eight and 16 years old in Porto Alegre/RS. In the first phase (cross sectional), the sample was classified as asthmatic if a physician had ever diagnosed them with asthma and if they reported symptoms and treatment for the disease in the past 12 months. In the second phase (control-case), the following were measured: anthropometry, physical activity levels, time spent in front of screens, and lung function (spirometry). Data are presented in mean and standard deviation or median and interquartile interval and by absolute and relative values. Chi-square, Student's t-test or Mann-Whitney test and Spearman correlation were applied, with p<0.05 being significant. Results: 605 students participated in the study, 290 children with a clinical diagnosis of asthma and 315 classified as a control. 280 (47.3%) were male children, with an average age of 11.0±2.3 years old. The spirometric values showed differences in the classifications of airway obstruction levels between the asthma and control groups (p=0.005), as well as in the response to bronchodilator use for FEV1/FVC (p=0.023). In the correlation assessment, there was no correlation between physical activity with anthropometric values, nor with pulmonary function, pre-and post-bronchodilator. Conclusions: The study demonstrates that there is no relationship between either anthropometric values or physical activity levels with pulmonary function of asthmatic children.